Penguatan Peran Pemuda dalam Pembangunan Desa melalui Karang Taruna - Muhammad Tafsir; Yana Fajriah; Sufiati Sufiati; Andi Dahrul; Dharmawaty Djaharuddin; Bungatang T; Yudi Akhmad Sadeli (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service aims to improve the role of Karang Taruna as a village development agent in Sanrobone Village, Takalar Regency. The problems faced by Karang Taruna in this village include low organizational capacity, minimal entrepreneurial skills, and lack of use of digital technology in promoting village potential. This activity was carried out through several stages, namely identification of needs, leadership and organizational management training, entrepreneurship workshops, digital marketing training, and implementation of real actions in the form of arranging mangrove tourism areas. The results of the activity showed a significant increase in participants' understanding of organizational management, preparation of work programs, development of business ideas based on local potential, and use of social media for promotion. In addition, participants succeeded in carrying out environmental conservation activities as part of efforts to develop village tourism. This activity is expected to be a model for empowering village youth based on Karang Taruna which can be replicated in other villages to encourage sustainable village development.